Intraspecific and interspecific interactions between Argyrodes antipodianus, a kleptoparasitic spider, and its New Zealand hosts : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Zoology at Massey University, Albany, New Zealand - Cooper, Daniel (Massey University, 2025)
Kleptoparasitism is a common foraging strategy in which one animal steals resources from another. Kleptoparasitism is therefore an important but often overlooked aspect of ecosystem dynamics. Ecosystem processes can be impacted by the interactions between invertebrate kleptoparasites and their hosts. One such interaction is that of the kleptoparasitic spider, Argyrodes antipodianus, common name “The Dew Drop spider” is native to Australia and introduced to New Zealand, which kleptoparasitises several species of web-building spiders. In my thesis, I test how A. antipodianus interacts with its New Zealand hosts and conspecifics. Firstly, I conducted a natural history survey to determine which hosts A. antipodianus commonly kleptoparasitise and how many A. antipodianus can kleptoparasitise a single host. I also tested whether the presence of A. antipodianus influenced the likelihood of a host abandoning its web and identified factors that influence kleptoparasitism by A. antipodianus (Chapter Two). I then investigated whether A. antipodianus can detect, recognise and are attracted to chemical cues from potential hosts and conspecifics (Chapter Three). Finally, I investigated the effects of kleptoparasitism by A. antipodianus on the fitness of their hosts and conspecifics (Chapter Four). I found that A. antipodianus kleptoparasitises the knobbled orb weaver Socca pustulosa more often than the New Zealand sheet web spider Cambridgea foliata. I also found that A. antipodianus tended to kleptoparasitise hosts alone, rather than in groups. Large host webs and host site fidelity both positively correlated with the presence of A. antipodianus in host webs. I did not find evidence that A. antipodianus responded to airborne chemical cues released by potential hosts or conspecifics. My results indicate that while A. antipodianus do not kleptoparasitise C. foliata well under lab conditions, there is little evidence to date that the presence of A. antipodianus negatively affect the foraging success of C. foliata. This suggests that interactions between A. antipodianus and its hosts differ with host species. I suggest that further research is needed to determine whether the relationship between A. antipodianus and C. foliata is kleptoparasitic, kleptobiotic or commensal.
Keywords: 310901 Animal behaviour